UPAYA GURU DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA MELALUI METODE ACTIVE LEARNING PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Hesti Septian, Kartika; Nazwa Salsabila, Anindia; Diana Tussalma, Adinda; Sofiana, Ika; Tsuraya Putri, Hana; Alfiana Ramadhani, Fika; Zahra, Khafinah; Rifiyati, Dian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the teacher-centered teaching process of Islamic Cultural History, which leads to student passivity and suboptimal learning outcomes. This situation indicates the need for learning innovations that can increase student engagement. This study aims to examine teachers' efforts to improve student engagement and learning outcomes through the application of Active Learning methods. The research method used is a library study, reviewing various relevant sources, such as scientific journals, theses, and previous research results. Learning methods are the means teachers use to educate students, using a variety of methods to avoid boredom and create a comfortable and enjoyable learning environment. The selection of appropriate methods will influence student understanding and interest in learning. The results show that the application of Active Learning through discussion activities, group work, question-and-answer sessions, and educational games can increase student participation in learning. Furthermore, this method also contributes to creating a more engaging, interactive, and enjoyable learning environment, thus impacting student understanding and learning outcomes. Thus, the teacher's role as a facilitator is crucial in managing active and effective learning.